OPTIMIZATION OF THE TAX BURDEN OF THE ENTERPRISE: LEGISLATIVE PREREQUISITES IN THE CONTEXT OF THE EUROPEAN EXPERIENCE - Tetiana Yakovets (Економіка та суспільство, 2021)
The article is devoted to the problems of the tax burden in Ukraine and the search for ways to adequately optimize it. In the current conditions of economic crisis, there is an urgent need to take measures to support economic entities. One of the current tools is taxation. The purpose of the presented research is to find legislative directions for optimizing the tax burden as a priority of the state in the context of promoting the development of economic entities. The existing attempts to legislatively reform the collection of value added tax and income tax as the main fiscal elements of the impact on the activities of economic entities are analyzed. The directions of improvement of the mechanism of collection of the VAT are offered and it is defined that gradual reduction of the rate annually on 1 point will lead during 2021-2025 to direct losses of tax receipts to the budget from the VAT. Global trends in tax burden optimization are studied. The main differences between the income tax and the withheld capital tax and the consequences of its introduction in Ukraine are analyzed. These recommendations increase the potential application of global trends in the process of reducing the tax burden on domestic enterprises.